2007
DOI: 10.7202/032956ar
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic and Structural Framework of Upper Middle Ordovician Rocks in the Head Lake-Burleigh Falls Area of South-Central Ontario

Abstract: Field investigations in the Head Lake-Burleigh Falls area of south-central Ontario, that focused mainly on the Covey Hill(?), Shadow Lake, Gull River and Coboconk formations along the Paleozoic escarpment, provided clear evidence of faulting. Observed and inferred structural deformation, coupled with faciès changes within the Shadow Lake and lower Gull River, point to a succession of basement movements during the Phanerozoic. These range from Hadrynian-Early Cambrian, through Middle Ordovician to post-late Mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…An earthquake-related interpretation is supported by previous investigations of the regional structural setting of Southern Ontario during the Ordovician-Silurian. Sanford (1993) showed that block faulting, uplift and arching were a common process in what is now Southern Ontario during that time span and which he related to several episodes of far-field stresses from late stage Taconic and Acadian orogenies. This resulted in the re-activation of Precambrian basement structures and block faulting of overlying Paleozoic strata at different times.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…An earthquake-related interpretation is supported by previous investigations of the regional structural setting of Southern Ontario during the Ordovician-Silurian. Sanford (1993) showed that block faulting, uplift and arching were a common process in what is now Southern Ontario during that time span and which he related to several episodes of far-field stresses from late stage Taconic and Acadian orogenies. This resulted in the re-activation of Precambrian basement structures and block faulting of overlying Paleozoic strata at different times.…”
Section: Discussionmentioning
confidence: 97%
“…This work is needed to identify underlying basement structures that might have a persistent record of reactivation during Paleozoic basin formation and which may provide insights into modern intracratonic seismic activity. Sanford (1993) showed that platformal Paleozoic strata that rest on Precambrian basement in Southern Ontario are extensively block faulted as a consequence of far field stresses during successive Appalachian orogenies and propagation of structures upwards into overlying sedimentary strata. Our work complements these findings by identifying prominent deformation structures interpreted as seismites in strata broadly synchronous with Appalachian deformation and faulting.…”
Section: Introductionmentioning
confidence: 99%
“…Local dips of Paleozoic rocks are greater where they are draped over Precambrian relief. The Paleozoic rock section thickens downdip towards the Appalachian and Michigan Basins south of Lake Ontario and west of Lake Huron respectively (Liberty, 1969;Johnson era/., 1992;Sanford, 1992).…”
Section: Bedrock Geologymentioning
confidence: 99%
“…1). Deer Bay is floored by upper Middle Ordovician sedimentary rocks (Sanford, 1992). The eastern shore of the bay is marked by a cliff of sedimentary rocks reaching 10 m above lake level.…”
Section: Description and Interpretation Of Seismic Profilesmentioning
confidence: 99%
“…dipping (15°-30°) seismic reflectors within the crystalline basement across the CMBBZ/NPLZ below Lake Ontario have been interpreted as ductile thrust faults (Milkereit et al, 1992). Brittle faulting in Precambrian rock and vertical displacements of upper Middle Ordovician rocks along major NNE-oriented lineaments within the CMBBZ provide evidence of post-upper Middle Ordovician reactivation of the CMBBZ (Wallach and Mohajer, 1990a;Wallach, 1991;Sanford, 1993). However, seismic data collected across the NPLZ below Lake Ontario indicate that a shale-limestone marker is undisturbed at the data resolution scale and that this zone has been relatively stable since the Ordovician period (Milkereit et al, 1992).…”
Section: Geological Settingmentioning
confidence: 99%